Application of THz spectroscopy for localisation of fibre optics embedded into glass fibre reinforced composite. (1st February 2019) - Mieloszyk, Magdalena; Majewska, Katarzyna; Ostachowicz, Wieslaw
Abstract: Recently, in many industrial branches (e.g. aviation, marine or civil engineering) metal elements are replacing by composite ones. To ensure their reliability structural health monitoring systems also based on fibre optics sensors (embedded into or mounted on composite structure) are widely applied. In the paper THz spectroscopy technique was proposed for detection and localisation of glass fibre optics embedded into a glass fibre reinforced polymer. The analysis was performed on a four-layer sample manufactured by infusion method. During this investigation both the sample surfaces roughness as well as fibre optics arrangements (according to the THz spectrometer axes) were examined. For this purpose THz images of internal structure of the sample were presented. Additionally two methods (in time and frequency domains) for quick determining of fibre optics location are presented. The first one is based on local changes in signal amplitudes while the second – on differences in power spectrum.